A surrogate of Roux-en-Y gastric bypass (the enterogastro anastomosis surgery) regulates multiple beta-cell pathways during resolution of diabetes in ob/ob mice - Chloé Amouyal; Julien Castel; Claudiane Guay; Amélie Lacombe; Jessica Denom; Stéphanie Migrenne-Li; Christine Rouault; Florian Marquet; Eleni Georgiadou; Theodoros Stylianides; Serge Luquet; Hervé Le Stunff; et al. (EBioMedicine, 2020)
Background: Bariatric surgery is an effective treatment for type 2 diabetes. Early post-surgical enhancement of insulin secretion is key for diabetes remission. The full complement of mechanisms responsible for improved pancreatic beta cell functionality after bariatric surgery is still unclear. Our aim was to identify pathways, evident in the islet transcriptome, that characterize the adaptive response to bariatric surgery independently of body weight changes. Methods: We performed entero-gastro-anastomosis (EGA) with pyloric ligature in leptin-deficient ob/ob mice as a surrogate of Roux-en-Y gastric bypass (RYGB) in humans. Multiple approaches such as determination of glucose tolerance, GLP-1 and insulin secretion, whole body insulin sensitivity, ex vivo glucose-stimulated insulin secretion (GSIS) and functional multicellular Ca2+-imaging, profiling of mRNA and of miRNA expression were utilized to identify significant biological processes involved in pancreatic islet recovery. Findings: EGA resolved diabetes, increased pancreatic insulin content and GSIS despite a persistent increase in fat mass, systemic and intra-islet inflammation, and lipotoxicity. Surgery differentially regulated 193 genes in the islet, most of which were involved in the regulation of glucose metabolism, insulin secretion, calcium signaling or beta cell viability, and these were normalized alongside changes in glucose metabolism, intracellular Ca2+ dynamics and the threshold for GSIS. Furthermore, 27 islet miRNAs were differentially regulated, four of them hubs in a miRNA-gene interaction network and four others part of a blood signature of diabetes resolution in ob/ob mice and in humans. Interpretation: Taken together, our data highlight novel miRNA-gene interactions in the pancreatic islet during the resolution of diabetes after bariatric surgery that form part of a blood signature of diabetes reversal. Funding: European Union's Horizon 2020 research and innovation programme via the Innovative Medicines Initiative 2 Joint Undertaking (RHAPSODY), INSERM, Société Francophone du Diabète, Institut Benjamin Delessert, Wellcome Trust Investigator Award (212625/Z/18/Z), MRC Programme grants (MR/R022259/1, MR/J0003042/1, MR/L020149/1), Diabetes UK (BDA/11/0004210, BDA/15/0005275, BDA 16/0005485) project grants, National Science Foundation (310030–188447), Fondation de l'Avenir.